Comparative Analysis Supporting Cohesion Policy Evaluation Based on STeMA Model: Insights from Tuscany and Emilia-Romagna - Francesco Dini; Silvia Grandi; Federico Martellozzo; Filippo Randelli; Patrizia Romei (Bollettino della Società Geografica Italiana)
This paper illustrates the work of the Florence Research unit, in particular the intermediate work of selection of indicators related to the topic “productivity”, for their inclusion in the STeMA model for the evaluation of territorial cohesion policies. As already indicated in the first working paper of this PRIN, we have combined for this selection the concept of “productivity” with that of “territorial competitiveness”, more correct for a survey about geographical economies (NUTS 3) as unit of analysis. The selection identified around 250 indicators, which were progressively reduced through a screening process. At the end, 12 indicators were included in the STeMA model. We have subsequently discussed the NUTS 3 geographical distribution of some of these indicators, inserting them within a synthetic reconstruction of the regional articulation of Italian development. Then we discussed deeper the cases of Tuscany and Emilia Romagna, emphasizing the aspects of analogy and diversity, both in the development model and in territorial policies.